Obiezione di coscienza nella legge 194 del 1978: considerazioni di diritto costituzionale a quarant’anni dall’approvazione della legge n. 194 del 1978 (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The article focuses on recent tendencies of the phenomenon of conscientious objection and tries to figure a balance after forty years since the enactment of law n. 194/1978. It points out that rights of women are directly protected by Constitution, while rights of conscientious objectors require the intervention of the Parliament. Starting from the apparently reassuring Report of the Ministry of Health to the Parliament, the A. underlines the problems and new challenges in this field, reaching the conclusion that the weak position of women and that the risk of illegal abortions imposes to enhance organisational standards of hospitals.
Keywords: Abortion; conscientious objectors; interpositio legislatoris; women’s rights; organisation of hospitals